Microcontroller gas detection system / Mohammad Afiq Mustakim - Mustakim, Mohammad Afiq (2013)
Natural gas has been playing a vital role in all aspects of development including power generation, transportation, industry and agriculture. When burned, it is one of the cleanest and most powerful forms of energy available. However, due to its volatile nature, it can also be dangerous, especially in cases of leakage. Gas leak detection system is important in order to avoid any unwanted cases from happening since gas leakage is one of the main causes of fire accidents and explosions. To solve this problem, a gas leak detection system is developed to detect the presence of gas along the pipeline. This project focuses on detecting gas leaks by using Microcontroller Based Gas Leakage Detection and Notification System. This gas detection system not only detects gas leaks, but also provides notification features such as alarm and voice synthesizer in order to alert users if there are any mishaps. Other elements included in this project are GSM auto SMS and monitoring system.